Factors affecting furfural as a nematicide on turf - Luc, J E (Journal of nematology, 2013)
Recently a furfural nematicide Multiguard Protect EC was launched for use on turfgrasses in the United States. A series of greenhouse experiments were conducted to determine the concentration and exposure time required for this formulation to irreversibly affect Belonolaimus longicaudatus, and to study factors that might affect the practicality of furfural use in turfgrass systems. One experiment exposed B. longicaudatus to increasing concentrations of furfural (0 to 990 ppm) in vitro for either 24 or 48 hr, followed by inoculation onto bermudagrass. A second experiment evaluated effects of exposure of B. longicaudatus to increasing concentrations of furfural in soil solution on bermudagrass with or without an organic thatch layer. A third experiment evaluated effects on B. longicaudatus of increasing concentrations of furfural applied as a spray treatment to creeping bentgrass. Results from the in vitro exposure experiment found decreasing numbers of B. longicaudatus with increasing furfural concentration beginning with the lowest concentration tested (270 ppm). Belonolaimus longicaudatus were virtually eliminated with furfural concentrations ≥ 720 ppm. Similarly, exposure to increasing concentration of furfural in soil solution resulted in increasing reduction in numbers of B. longicaudatus. Presence of thatch slightly reduced the population density of B. longicaudatus. Spray application of furfural only reduced numbers of B. longicaudatus at the two highest rates (3,600 and 4,950 ppm)